A quest for a direct observation of the Unruh effect with classical electrodynamics: In honor of Atsushi Higuchi 60th anniversary - Cozzella, Gabriel [UNESP]; Landulfo, Andre G. S.; Matsas, George E. A. [UNESP]; Vanzella, Daniel A. T. (World Scientific Publ Co Pte Ltd, 2018)
The Unruh effect is essential to keep the consistency of quantum field theory in inertial and uniformly accelerated frames. Thus, the Unruh effect must be considered as well-tested as quantum field theory itself. In spite of it, it would be nice to realize an experiment whose output could be directly interpreted in terms of the Unruh effect. This is not easy because the linear acceleration needed to reach a temperature of 1K is of order 10(20) m/s(2). We discuss here a conceptually simple experiment reachable under present technology, which may accomplish this goal. The inspiration for this proposal can be traced back to Atsushi Higuchi's Ph.D. thesis, which makes it particularly suitable to pay tribute to him on occasion of his 60th anniversary.
Keywords: Unruh effect